Augmented Reality for Manual Assembly in Industry 4.0: Gathering Guidelines - Agati, Salvador; Bauer, Rudieri; Hounsell, Marcelo; Paterno, Aleksander (Anais do Simpósio de Realidade Virtual e Aumentada (SVR), 2020)
The manufacturing industry always reinvented itself to maintain competitiveness, constantly lowering its production costs. With the significant improvement in the reliability and stability of facilities, human error has become one of the most critical factors for quality assurance. About 70% to 90% of quality defects in assembly production systems are directly or indirectly caused by human errors. In the last decades, the interest in using Augmented Reality (AR) in many application areas, including the industry, has increased. Although AR is recognized as an important technology, there is an evident gap in design guidelines and methodologies in this field. The objective of this paper is to find guidelines to help in designing AR-based manual assembly systems. We did a systematic literature mapping over scientific review papers, from 2015 to 2020, and found 14 review papers. The guidelines found were classified into four groups: usability, cognitive, ergonomics, and corporate-related. Off the 14 papers, 11 of them (78,6%) presented guidelines. Limitations of this work are the low number of review papers found and the probability of having new guideline categories not found in this paper. We conclude that a comprehensive set, that encompasses general and specific guidelines depends on the characteristics of the assembly line being implemented. The suggested group of general guidelines based on previous work may be useful when designing AR-based manual assembly systems.